The golden age - Grahame, Kenneth; Stone and Kimball Collection (Library of Congress); Stone & Kimball (Stone & Kimball; John Lane, 1896)
The adventures of five brothers and sisters growing up in rural England in the late nineteenth century.
"First edition, May [1895] ... Third edition, January [1896]"
Kramer, S. Stone & Kimball & Herbert S. Stone & Co. bib., 1893-1905,43
Kramer, S. Stone & Kimball & Herbert S. Stone & Co. bib., 1893-1905,43
The adventures of five brothers and sisters growing up in rural England in the late nineteenth century.
Keywords: Country life / Fiction; Siblings / Fiction; England / Fiction.; Publishers' cloth bindings (Binding) / rbbin; Bildungsromans / gsafd; Pastoral fiction / gsafd; Juvenile works / fast / (OCoLC)fst01411637; Fiction / fast / (OCoLC)fst01423787